Searching for Dark Galaxies with H I Detection from the Arecibo Legacy Fast ALFA (ALFALFA) Survey - Minseong Kwon; Ho Seong Hwang; Brian R. Kent; Ilsang Yoon; Gain Lee; Hyein Yoon (The Astrophysical Journal Supplement Series)
We present a catalog of 142 dark galaxy candidates in a region covered by the Arecibo Legacy Fast ALFA (ALFALFA) survey. We start with 344 ALFALFA H i sources without optical counterparts and remove those that do not seem to have a dark galaxy origin. To do that, we first eliminate 83 sources that are known H i clouds probably formed from tidal interactions between galaxies and 13 sources that have optical counterparts. We then remove 56 sources located near other H i sources, which are likely to be H i clouds. We further exclude 10 sources that have nearby H i sources within the ALFALFA beam and 40 sources potentially associated with nearby galaxies. We perform visual inspection of optical images from the DESI Legacy Imaging Survey with an r -band surface brightness limit of ∼28.5 mag arcsec ^−2 as well as near-ultraviolet images from GALEX to confirm the absence of stellar emission. We additionally inspect infrared images from the Wide-field Infrared Survey Explorer and AKARI for dust emission. As a result, we identify 142 dark galaxy candidates and analyze their physical properties by comparing them with luminous galaxies. We find that the dark galaxy candidates generally have smaller dynamical masses, higher H i -to-dynamical mass ratios, and are located in less dense regions when compared to luminous galaxies, which is consistent with results from cosmological simulations. This sample provides an important testbed for studying the role of dark matter in galaxy formation and evolution.